1981
DOI: 10.1007/bf01342673
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on cholinergic activities in the central nervous system ofLocusta migratoria

Abstract: Summary.Comparative studies on biochemical and pharmacological aspects of cholinergic transmission in the cerebral ganglion of locust and the mouse cerebral cortex were performed. The results point to common features and significant differences in the cholinergic pharmacology of insect and vertebrate nervous system: ACh content as well as AChE and ChAT activities reflect a highly cholinergic innervation of the locust cerebral ganglion. While the nicotinic AChreceptor type predominates in locust nervous system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Putative cholinergic neurons are widely distributed in the adult CNS and the PNS. Since ACh has been considered to be a major excitatory neurotransmitter in the CNS and sensory afkrents of insects (Sanes and Hildebrand, 1976: Breer, 1981: Breer and Sattelle, 1987, our results appear reasonable. Although X-gal staining is observed in many primary sensory afferents in transformants carrying construct I , it is not present in all systems but seems to be related to the modality of the primary sensory neurons.…”
Section: Discussionsupporting
confidence: 73%
“…Putative cholinergic neurons are widely distributed in the adult CNS and the PNS. Since ACh has been considered to be a major excitatory neurotransmitter in the CNS and sensory afkrents of insects (Sanes and Hildebrand, 1976: Breer, 1981: Breer and Sattelle, 1987, our results appear reasonable. Although X-gal staining is observed in many primary sensory afferents in transformants carrying construct I , it is not present in all systems but seems to be related to the modality of the primary sensory neurons.…”
Section: Discussionsupporting
confidence: 73%
“…Comparative studies have shown that the specific activity of ChAT (Fig. 1) is more than 100 times higher in insect ganglia than it is in the vertebrate brain (57). The enzyme is present in neuronal perikarya (where it is synthesized), neurites and nerve endings, where the highest activity of ChAT is found.…”
Section: Enzymology Of Chatmentioning
confidence: 96%
“…1C) may result from nicotinic effects masking muscarinic effects (see also Benson, 1992;Heinrich et al, 1997;Heinrich et al, 2001;Wenzel et al, 2002) owing to the greater abundance of nicotinic receptors (Breer, 1981), and the action of acetylcholinesterase (Treherne and Smith, 1965), which would not affect the non-hydrolysable acetylcholine analogue carbachol. Supporting this, the cholinesterase inhibitor eserine (1 mmol l -1 ), which leads to accumulation of spontaneously released acetylcholine in the synaptic cleft, readily induced flight.…”
Section: Acetylcholine and The Tcg Interneuronementioning
confidence: 99%